Study of the flexural behaviour of steel fibre reinforced concrete (SFRC) segment tunnel lining - Lee, Benjamin Jun Wen. (2010)
The objective of this report was to determine the material and structural properties of SFRC and also to study the behavior of SFRC in order to establish the required performance characteristics and specifications for tunnel lining applications.